PENGARUH IMPLEMENTASI REGROUPING DALAM EFEKTIFITAS BELAJAR MENGAJAR SEKOLAH DASAR DI UPTD SDN 122377 PEMATANGSIANTAR - Simanjuntak, Melvin; Redina Rumahorbo; Yulan Sitinjak; Valentina Silalahi; Ananda Rizki Amalia5; Sri Jesicca Matondang; Olive Dwi Nera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is research with evaluation and observation which aims to determine the influence of the regrouping policy on the effectiveness of teaching and learning, the reasons for implementing regrouping, the positive and negative impacts of implementing regrouping, the challenges faced by teachers and students in the regrouping policy, as well as the success indicators used to assess elementary school regrouping policy at state elementary school uptd 122377 P.Siantar. This research uses the quantitative research model with the research subject being UPTD SDN 122377 P.Siantar, Siantar Martoba subdistrict. The data collection method is by interviews, observation and documentation with the analysis techniques used are data reduction, presentation and drawing conclusions based on the available data. This research found that state elementary school 122377, state elementary school 122378, state school 122370 were regrouped into one school, namely UPTD SDN 122377 P.Siantar. This policy has been designed since 2021 and then the government implemented this program in 2022 until now. These three schools have agreed to merge into one school. Then, the condition of students, teaching staff, regulations of the Minister of Home Affairs, and school environmental conditions are factors that influence the regrouping program. The effectiveness of teaching and learning with a regrouping policy is a complex topic and the results depend on the factors that influence the success of this regrouping policy. There is no universal answer, because the success of regrouping is greatly influenced by how the policy is implemented and the context of the school's achievements. Although regrouping has the potential to increase learning effectiveness, its success depends on careful planning, proper implementation, and support from all parties involved. Comprehensive evaluation, including measurement of learning achievement, classroom observations, and feedback from teachers to students, is very important to determine the effectiveness of regrouping at the UPTD SDN 122377 P.Siantar elementary school. From the research results, it can be seen that the government's reasons for implementing the regropung policy at Uptd Sdn 122377 P. Siantar are: (1) based on surveys or observations from the education service that these three schools are in the same area or location (2) and when accepting new students it is always There was conflict between these three schools in their scramble to accept new students in grade 1 elementary school. (3) and improving the quality of education in literacy and numeracy at Uptd Sdn 122377 P.siantar.